Projeto de uma aeronave biplana rádio controlada para participar da competição SAE Brasil Aerodesign 2019 - Gonçalves, Lucas de Andrade [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Each year in the aerodesign project, student teams from several universities from Brazil and the world are challenged to design airplanes more and more audacious due to the challenging rules of the competition. In 2019, the biplane configuration seems very promising. However, the Aerofeg team never validated the study of non-conventional aircrafts such as biplanes and flying wings. This way, this document aims to analyze and develop a design methodology that includes these configurations, focusing on the stages of pre-design, conceptual design and preliminary design, which comprise the selection of the aircraft configuration as well as its base dimensions. The design methodology developed is based on a multidisciplinary optimization by a genetic algorithm, whose objective is to create a large population of aircrafts of different configurations focusing on the maximization of the flight score in the competition. The aircraft designed, the first team’s biplane aircraft to fly in a competition, achieved the second place overall and transported the second highest payload in the SAE Brasil aerodesign 2019 competition. This result qualified the Aerofeg team to participate of the fourth international competition of its history.

N o projeto aerodesign, a cada ano as eq uipes de estudantes de diversas universidades do Brasil e exterior são desafiadas a desenvolver projetos cada vez mais ousados devido as desafiadoras regras da competição. Para 2019 a configuração biplana se mostra promissora. Contudo, o estudo de aeronave s não convencionais como biplanos e asas voadoras nunca foi validado pela equipe A erofeg. Deste modo, este trabalho visa analisar e desenvolver uma metodologia de projeto que abranja estes tipos de configuração, focando nas fases de pré projeto, projeto co nceitual e projeto preliminar que abrangem a escolha da configuração da aeronave bem como suas dimensões bases. A metodologia de projeto desenvolvida se baseia em uma otimização multidisciplinar via algoritmo genético, cujo objetivo é gerar uma extensa pop ulação de aeronaves de diferentes configurações buscando a maximização da pontuação de voo na competição. O projeto desenvolvido, a primeira aeronave biplana da equipe a validar um voo na competição, obteve a segunda posição geral e transportou a segunda m aior carga paga na competição SAE Brasil A erodesign 2019 qualificando a equipe A erofeg para participar da quarta competição internacional de sua história.
Design of a radio controlled biplane aircraft to participate in the SAE Brasil Aerodesign 2019 competition
Keywords: Multiplane; Project optimization; Competition; VANT; Multiplano; Otimização de projeto; Aeronaves; Competições; Projetos de engenharia; Algoritmos genéticos